Safety and Efficacy of Regadenoson for Pediatric Stress Perfusion Cardiac MRI with Quantification of Myocardial Blood Flow - Shivani G. Patel; Nazia Husain; Cynthia K. Rigsby; Joshua D. Robinson (Children, 2022)
Myocardial stress perfusion magnetic resonance imaging is a non-invasive tool to assess for myocardial ischemia and viability. Pediatric myocardial stress perfusion MRI can be challenging due to multiple intravenous lines, sedation, inadequate breath holding, fast heart rates, and complex anatomy. We performed a retrospective analysis in 39 children to evaluate safety and efficacy of regadenoson, a coronary vasodilator administered via a single intravenous line (6–10 mcg/kg), with respiratory motion correction (MOCO) and semi-quantitative blood flow analysis. Stress response data and adverse events were recorded, and image quality compared between native and MOCO reconstructions, assessing for perfusion deficits. Semi-quantitative analysis compared myocardial perfusion reserve index (MPRI) between patients who had a focal perfusion defect, patients who had undergone an orthotopic heart transplant, and non-transplant patients with no focal defects. Stress perfusion was completed in 38/39 patients (median age 15 years with a 41 ± 27% rise in heart rate (p < 0.005). Fifteen out of thirty-eight had transient minor side effects with no major adverse events. MOCO image quality was better than non-MOCO (4.63 vs. 4.01 at rest, p < 0.005: 4.41 vs. 3.84 at stress, p < 0.005). Reversible perfusion defects were seen in 4/38 patients with lower segmental mean MPRI in the area of the perfusion defect, nearing statistical significance when compared to non-transplant patients with no defects (0.78 ± 0.22 vs. 0.99 ± 0.36, p = 0.07). The global MPRI of the 16 patients who had undergone orthotopic heart transplant was significantly lower than the non-transplant patients (0.75 ± 0.22 vs. 0.92 ± 0.23, p = 0.03). Regadenoson is a safe and effective coronary vasodilator for pediatric stress perfusion MRI with MOCO producing better image quality and allowing for semi-quantitative assessment of perfusion deficits that correlate with qualitative assessment.